CROSS-BORDER CULTURAL EXPANSION VIA AI-DRIVEN PLATFORMS: A COMPARATIVE ANALYSIS OF ENGLISH LANGUAGE GLOBALIZATION - Rustamov Alijon Amonkulovich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article evaluates the structural mechanisms through which artificial intelligence platforms accelerate cross-border cultural expansion and the globalization of the English language. Grounded in digital sociolinguistics and soft power theory, the study executes a comparative analysis between foundational large language models and dedicated adaptive educational platforms. The research analyzes how automated neural text generation, algorithmic translation pipelines, and real-time speech synthesis reinforce Western linguistic hegemony by standardizing global communication around Anglo-American semantic templates. The findings indicate that while artificial intelligence democratizes access to international networks, it simultaneously accelerates the erosion of localized syntactic variations and minority cultural concepts.